Efektivitas Pembelajaran Mengaji Metode Tilawati di Masjid SD Muhammadiyah 9 Kota Malang - Roihana; Abdurrohim; Adillah, Hilya (JURNAL PUSAKA, 2023)
The implementation of learning to recite the Al Qur’an is more effective and efficient in the mosque than in the classroom. Because in the mosque, teachers can convey material more freely and are closer to students. Inside the mosque it can also make it easier to adjust the sitting position for the classical learning model and also students feel more comfortable because of the new atmosphere. Based on the background above, the purpose of this research is to know and understand the effectiveness of learning to recite the tilawati method carried out in elementary the mosques Muhammadiyah of nine City of Malang. Qualitative research with a descriptive approach is used with the aim of explaining and describing existing events, both practical and engineered. This data collection technique is used to obtain data as needed. This data includes: Observations, Interviews, Documentation. Research findings. This learning of the Al Qur’an produces effectiveness in the learning process, because the place is more comfortable and provides students, and is more conditioned for students who are busy or joking around themselves. This tilawati method has several volumes, namely volumes one to volume the six and after volume the six is finished, students continue to the Al-Quran. This Al Qur’an class is different from the formal class, both in terms of the number of students, the location of implementation and the number of classes of Al Qur’an. In this Al Qur’an class each teacher teaches a maximum of twenty children. In contrast to formal classes, where one class consists of approximately the thirty children. Key words: children; education; effectivity; elementary school; students